Incorporating patient and caregiver feedback into lung transplant referral guidelines for individuals with cystic fibrosis—Preliminary findings from a novel paradigm. Issue 10 (17th August 2020) - Smith, Patrick J.; Dunitz, Jordan M.; Lucy, Amy; Hempstead, Sarah E.; Tallarico, Erin; Faro, Albert; Pilewski, Joseph M.; Ramos, Kathleen J.
Abstract: Background: Lung transplantation is a common therapeutic option for individuals with cystic fibrosis (CF) and advanced lung disease, yet many individuals with CF are not appropriately referred for evaluation. The present study sought to enhance CF transplant referral guidelines by integrating patient‐centered input to identify possible psychosocial barriers contributing to suboptimal referral for appropriate CF transplant candidates. Methods: As a component of developing the Cystic Fibrosis Foundation (CFF) Lung Transplant Referral Consensus Guidelines, we convened a focus group of lung transplant recipients with CF and two spouses of CF recipients. Each session involved standardized approaches to elicit qualitative, thematic content. Results: CF patients and caregivers characterized five areas for improvement, which were integrated into formal CFF referral guidelines. These included (a) timing of transplant discussion with CF providers, (b) accuracy of transplant‐related knowledge and expectations, (c) stigma associated with the need for transplantation, (d) treatment team transition issues, and (e) social support and mental health concerns. Earlier introduction of transplant, greater details regarding manageable aspects of treatment, and greater provision of social support were all associated with better psychosocial experiences. Conclusions: Integrating patient‐centered input into guideline development yielded important and previously unknown psychosocial barriers contributing to suboptimal transplant referral.